Artificial Intelligence for a Better Employee Engagement - Sari, Ria Emilia; Min, Siu; Purwoko, Hiskia; Furinto, Asnan; Tamara, Dewi (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2020)
Employee engagement is the positive attitude of each employee towards the business and the value of the organization. This research aims to see whether the use of AI-based technology, tools, and software can help management detect intangible things such as employee engagement level and provide clues as to what factors influence it and how management can improve it. This research is a qualitative approach. We interviewed the management and selected employees to determine employee engagement at SML before andafter implementing the AI-based application. The interview results compared with the results obtained from the application for six months (Feb - July 2020). The study was conducted on all SML employees, amounting to 39 people. This research has shown that the use of AI based software can significantly help management, not only to find out the status of each employee’s level of involvement but also to anticipate their attitudes and behaviors through predictive indicators. Thus, the company can proactively retain key employees. This research provides new and practical insights and opportunities for company owners and leaders to utilize technology to detect something that is naturally quite difficult because it requires specific knowledge and experienceKeywords: engagement, employee engagement, work engagement, technology, technology enabler, artificial intelligence, software, application.* Magister Manajemen BINUS Business School, Universitas Bina Nusantara, Jl. Hang Lekir I No. 6, Senayan, Kebayoran Baru, Jakarta Selatan, DKI Jakarta. https://doi.org/10.21632/irjbs.13.2.173-188